If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -8 = 10x + 9 Reorder the terms: -8 + 11x = 10x + 9 Reorder the terms: -8 + 11x = 9 + 10x Solving -8 + 11x = 9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -8 + 11x + -10x = 9 + 10x + -10x Combine like terms: 11x + -10x = 1x -8 + 1x = 9 + 10x + -10x Combine like terms: 10x + -10x = 0 -8 + 1x = 9 + 0 -8 + 1x = 9 Add '8' to each side of the equation. -8 + 8 + 1x = 9 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = 9 + 8 1x = 9 + 8 Combine like terms: 9 + 8 = 17 1x = 17 Divide each side by '1'. x = 17 Simplifying x = 17
| (23-b)*b=130 | | -10v-2v-7v= | | -2x+3=-x+8 | | 5d+10d-17d= | | ln(4x+7)=8 | | 2n+6n+n= | | 6s+5-(s+6)= | | (x^2-3x+2)*(x^2-3x+6)=60 | | 100-19.62x^2=0 | | -2x-1+x=-7+6-x | | 2(x-3)=1-(x+3) | | 4x-3-x=3x-4 | | (4a+8)=(6a-32) | | 4b=5b-7 | | 5+3x=-x-3 | | 2y=3(10-y) | | 7x+5=93 | | X^2-7x+21=99 | | 9-(y+2)=0 | | 2lnx=ln(4x+3) | | (5x-5)(4x-5)= | | 2lnx=4(4x+3) | | Y=-4/3(1.33)-8 | | 12x=150+4x | | y=-1/3[x]-3 | | 5a-3a-2a+6+7b= | | -5x+10(0)=-50 | | 4x^3+2x^2+2x-1=0 | | -6(2t+9)=-18 | | 4(f-4)=-24 | | 22+(-8)+32-(12)+8= | | 6(3s+6)=126 |